Respostas de pastagem natural, localizada em área da depressão central do Rio Grande do Sul, à adubação e à disponibilidade hídrica - Souza, Iraline Brum de (2008)
This study was conducted in the city of Restinga Sêca, RS, with the objective to analyze the productivity, quality, botanical composition and biological characteristics of native pasture in response to fertilization and water availability. The fertilization increased native pastures productivity. The dry matter total accumulation rate, at dry or wet area, both fertilized, was 102 kg/ha/day. In the same areas, not fertilized, was 47 and 41 kg/ha/day, respectively. For green matter, the fertilization also increased the productivity, reaching accumulation rates of 70 and 93 kg/ha/day for dry and wet areas, respectively. In these not fertilized areas, the rates were 29 and 25 kg/ha/day. Furthermore, increased nitrogen and crude protein rates in plant tissues and mineral matter quantity in the plots. Water availability influenced on pasture components, as the water availability was increased, lower amount of components such as strait leaf, broad leaf and legumes and higher amount of neutral detergent fiber in tissues were observed, especially in spring period. Fertilization as well as water availability decreased the wealth of species, causing domination of some species already adapted to these conditions. Two functional groups were formed with vegetal biological characteristics, a group of capture of resources, with a high specific leaf area (SLA) (26) and low dry matter content (DMC) (234), composed by Paspalum pumilum, Paspalum urvillei, Paspalum pauciciliatum, Axonopus affinis and Setaria glauca. The other group is the conservation of resources, low SLA (21) and high DMC (323), composed by Paspalum notatum and Andropogon lateralis.